Synthesis and Study of Anticancer and Antioxidant Activities of 2-oxoquinoline Hydrazide Derivatives - Mohamed, Marwa Khalil; Salem, Ezzeldin Mohamed S.; Ali, Ibrahim Ahmed I. (UI Scholars Hub, 2023)
In this work, hydrazone, thiosemicarbazide, diamide, and dipeptide derivatives were prepared from the glycine and β-alanine hydrazide of 4-hydroxy-2-oxoquinoline. The desired derivative resulted from substitution, hydrazinolysis, condensation, and azide coupling reactions. The fabricated derivatives were screened for anticancer characteristics toward human’s colon carcinoma (HCT-116) cell line using the 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide viability assay, while antioxidant property was examined using an in vitro H2O2 scavenging method. The β-alanine hydrazide derivative 3a showed a remarkable IC50 value of 18.8 μg/mL, whereas its corresponding thiosemicarbazide 5b exhibited moderate activeness with an IC50 value of 26.89 μg/mL. Conversely, the dipeptide derivative 7 with a Gly-β-Ala sequence showed better activity than the β-Ala-Gly derivative 8a. The IC50 values of 27.28 and 61.4 μg/mL, respectively, were achieved. According to an H2O2 scavenging activity test, the hydrazide of β-Ala derivative 2a displayed the best H2O2 scavenging property, with an IC50 value of 38.7 μg/mL.